2018
DOI: 10.1016/j.vetpar.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Taenia solium from a community perspective: Preliminary costing data in the Katete and Sinda districts in Eastern Zambia

Abstract: The tapeworm Taenia solium is endemic in Zambia, however its socioeconomic cost is unknown. During a large-scale interventional study conducted in Zambia, baseline economic costs of human and porcine T. solium infections were measured. Questionnaire surveys were conducted within three neighbourhoods in Zambia's Eastern province in 2015 and 2016. A human health questionnaire, capturing costs of clinical symptoms commonly attributable to human cysticercosis and taeniasis, was conducted in randomly selected house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The actual disease burden and economic impact of T. solium in Zambia still needs to be determined. A recent study by Hobbs et al (2018a) has highlighted some preliminary data based on human health questionnaires (n = 267) and pig socio economic questionnaires (n = 271) implemented in the Eastern Province. Sixty-two percent of the respondents of the human health questionnaire had reportedly experienced some of the surveyed symptoms typically associated with NCC (e.g.…”
Section: Taenia Solium In Zambia: What Do We Know?mentioning
confidence: 99%
See 1 more Smart Citation
“…The actual disease burden and economic impact of T. solium in Zambia still needs to be determined. A recent study by Hobbs et al (2018a) has highlighted some preliminary data based on human health questionnaires (n = 267) and pig socio economic questionnaires (n = 271) implemented in the Eastern Province. Sixty-two percent of the respondents of the human health questionnaire had reportedly experienced some of the surveyed symptoms typically associated with NCC (e.g.…”
Section: Taenia Solium In Zambia: What Do We Know?mentioning
confidence: 99%
“…Under Zambian conditions, high levels of African Swine fever lead to a high pig turnover in the pig population, causing an insufficient proportion of the pig population that is actually protected on the one hand, and reluctance of the pig owners to apply any intervention via injections on their pigs (Hobbs et al, 2018a, Hobbs et al, 2018b, submitted); porcine vaccination is therefore not considered a feasible and effective strategy. This is corroborated by simulations in the transmission models (Fig.…”
Section: The Potholed Road To Success?mentioning
confidence: 99%
“…Figure 4 presents key research gaps and data needs to move the field forward. Matthew A Dixon (m.dixon15@imperial.ac.uk; corresponding author) 1,2 , Uffe C Braae (ucbraae@gmail.com) 3,4 , Peter Winskill (p.winskill@imperial.ac.uke-mail) 2 , Brecht Devleesschauwer (brecht.devleesschauwer@sciensano.be) 5,6 , Chiara Trevisan (ctrevisan@itg.be), 7 Martin Walker (mwalker@ rvc.ac.uk) 1,8 , Inge Van Damme (inge.vandamme@ugent.be), 6 Sylvia Ramiandrasoa (sylviaramianoro@gmail.com), 9 Veronika Schmidt (veronika.schmidt@tum.de) 10,11 , Andrea S Winkler (andrea.winkler@tum.de) 10,11 , Maria V Johansen (mvj@sund. ku.dk), 12 Sarah Gabriël (sarah.gabriel@ugent.be), 6 Wendy E Harrison (w.harrison@schisto.org.uk), 13 Maria-Gloria Basáñez (m.basanez@imperial.ac.uk; corresponding author) 1,2 This paper is well written and very interesting to read as it brings to the fore Reviewer's summary.…”
Section: Future Directionsmentioning
confidence: 99%
“…Recent reviews have suggested that TS may also be present in other regions, such as Eastern Europe 6 . Large economic consequences do not only pertain to the human public health sector, but also to the animal sector, resulting from reduced market value and market distortion associated with pig infection in the food-value chain, which disproportionately impacts the poorest farmers and communities [7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…As such, cysticerci have the potential to develop in the brain (central nervous system), collectively named neurocysticercosis (NCC), with epilepsy, migraine, and other neurological manifestations as a consequence. Furthermore, not only NCC, but also porcine cysticercosis (PCC), has an enormous economic impact due to many related costs, such as hospitalization and loss of condemned carcasses [50,51]. Therefore, the increase in public awareness of these consequences has led to the implementation of prevention and control measures (such as pig confinement, vaccination, and treatment; human treatment; and health education) against T. solium in more and more countries.…”
Section: Introductionmentioning
confidence: 99%